1992
DOI: 10.1901/jaba.1992.25-599
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Consultation as a Method of Improving Performance of Staff Members in a Group Home

Abstract: A model of ongoing consultation was implemented in a community group home for 8 adults with severe and profound mental retardation. Two consultants, highly experienced in working with people with mental retardation and in the procedures used in group homes, taught staff members to use a token reinforcement system, to engage the adults in a variety of activities, and to improve the content and style of the staff members' interactions with the adults. The consultants taught skills to 9 staff members through brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…A further meeting was also held for all TAs and the respective school SENCos to recap on the training conducted and an outline of the research design, school-based requirements and support to be offered by the researcher was provided. In order to ensure treatment fidelity (Harchik, Sherman, Sheldon, & Strouse, 1992;Schinke, Botvin, & Orlandi, 1991) various actions were taken, such as:…”
Section: Background and Initial Stepsmentioning
confidence: 99%
“…A further meeting was also held for all TAs and the respective school SENCos to recap on the training conducted and an outline of the research design, school-based requirements and support to be offered by the researcher was provided. In order to ensure treatment fidelity (Harchik, Sherman, Sheldon, & Strouse, 1992;Schinke, Botvin, & Orlandi, 1991) various actions were taken, such as:…”
Section: Background and Initial Stepsmentioning
confidence: 99%
“…Many studies have shown that without self-generated feedback staff required frequent posttraining supervisory feedback, ranging from twice a week to once every two weeks, for staff and client behavior to be maintained (e.g., Green, Reid, Perkins, & Gardner, 1991;Hall & Macvean, 1997;Harchik, Sherman, Sheldon, & Strouse, 1992;Hrydowy & Martin, 1994;Ivancic, Reid, Iwata, Faw, & Page, 1981;Methot, Williams, Cummings, & Bradshaw, 1996;Page, Iwata, & Reid, 1982). Arguably, self-generated feedback should enhance generalization of staff performance by evoking and reinforcing behavior that would otherwise not occur in the absence of supervisors.…”
Section: Self-generated Feedbackmentioning
confidence: 99%
“…Repp et al [1981] found that staff rarely used the form of instruction most likely to help residents respond correctly (nonverbal instruction either with or without physical assistance) and usually employed the form of instruction (verbal instruction) that most likely led to non-response. Various studies have demonstrated the beneficial impact of training or supervising staff to provide assistance or praise for participation, schedule activity, and organize their responsibilities for supporting resident activity [e.g., Porterfield et al, 1980;Parsons et al, 1989;Harchik et al, 1992;Anderson et al, 1997;Jones et al, 1999]. Holland and Meddis [1993] concluded that people who spent more time engaged in household activities lived in community houses that had procedures to encourage participation, such as schedules of household tasks and staff actively supporting people to undertake them.…”
Section: (D) Staff Procedures and Performancementioning
confidence: 99%